THE EFFECT OF WORK DISCIPLINE AND THE WORK ENVIRONMENT ON EMPLOYEE JOB SATISFACTION (CASE STUDY OF PT. INFOMEDIA NUSANTARA) - Tarmidi, Didi; Hasanudin, Raihan; Budiana, Desandi; Nugraha, Reksianda; Arzad, Muhamad Fikri; Fauzi, Restu (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research aims to determine how the description of work discipline, work environment, and employee job satisfaction, as well as to determine how the effect of work discipline and work environment on employee job satisfaction. Infomedia Nusantara. The factors tested in the study were work discipline and work environment as independent variables, while job satisfaction was dependent variables. The research methods used in this research are descriptive and verification methods. The population in this study were employees at PT. Infomedia Nusantara. The sampling technique used in this study was Purposive Sampling and the size of the sample in this study was calculated with the formula Slovin, so the total number was 133 respondents. The analytical methods used in this study are some linear regression analyses using SPSS25 for Windows. The results of this study show that work discipline and work environment have an effect on employee job satisfaction at PT. Infomedia Nusantara. The effect of work discipline and the work environment on employee job satisfaction was 37.5%.